SISTEM APLIKASI ANDROID SERVICE PROVIDER BIZNET PADA PT SUPRA PRIMATAMA NUSANTARA - Wahyu Nur Cholifah; Sri Mardiyati; Ulfa Pauziah (Jurnal Ilmiah Global Education, 2023)
The purpose of this research is to develop an Android application system for service provider Biznet at PT Supra Primatama Nusantara using Java programming language. This application is designed to help users with various activities such as registering for services, managing accounts, choosing packages, paying bills, and filing customer complaints. This study uses the waterfall system development method, which consists of needs analysis, system design, implementation, testing, and maintenance. The result of this research is an Android application for Biznet service providers that can be used by users to access Biznet services easily and efficiently. This application has been successfully implemented and tested, and is able to overcome the problems faced by users in accessing Biznet services. This application also has a user-friendly interface that can be operated easily. The conclusion of this research is that the development of the Android application service provider Biznet at PT Supra Primatama Nusantara using the Java programming language was successfully carried out using the waterfall method. This app can help users efficiently and easily access Biznet services. This research also shows that using the Java programming language can provide benefits in developing effective and efficient Android applications.